(untitled) - Reston, James (New York, 1969)
This collection of Mr. Reston's writings from The New York Times and other publications displays his endlessly curious mind, his pragmatic view of issues, and the distinguished quality of his reporting.He is particularly concerned with the problems of change, which seem to him the central issue of the age. While he realizes that no generation of American officials ever had to face such a torrent of intractable new problems, he reaffirms the reporter's right to advise and criticize. He writes on such varied subjects at the responsibility of the press, the women of Washington, the problems of education, and the pitfalls of power. His portraits of John F. Kennedy, Dean Acheson, Robert Frost, and other figures are superb examples of his insight and sensitivity.Sketches in the Sand is a wise and witty book which demonstrates that James Reston is one of the most graceful and intelligent writers in America.